Associative organisational models in Italian forests for addressing land abandonment - Loreggian, Francesco (Acta silvae et ligni, 2024)
This paper investigates associative organisational models as a potential governance solution to the issue of land abandonment. Land fragmentation, along with inadequate or absent management, are key problems that hinder forest stability and resilience in many countries, particularly in Southern Europe. Land abandonment further exacerbates these issues, increasing climate change-related risks, such as forest fires. After reviewing the broader European context, the paper focuses on Italy, where this problem is particularly acute. Based on a qualitative content analysis of the literature and policy documents, the paper outlines the available solutions for promoting active forest management through associations, as outlined by Italian forest law. Several types of associative models exist, facilitated by recent policy initiatives, including forest consortia, forest associations and cooperatives, and various instruments for regulating partnerships and associative management. However, limited data on land abandonment and forest ownership, especially regarding private ownership, hampers effective implementation and monitoring, highlighting a significant research gap in this area.
Keywords: asociativno upravljanje gozdov; razdrobljenost zemljišč; rešitve združevanja; zasebni lastniki gozdov